2020
DOI: 10.1002/etc.4731
|View full text |Cite
|
Sign up to set email alerts
|

POCIS Calibration for Organic Compound Sampling in Small Headwater Streams

Abstract: Field‐based atrazine sampling rates (Rs) obtained by the polar organic chemical integrative sampler (POCIS) method were measured in 9 headwater streams over 3 yr covering 5 to 6 exposure periods of 2 to 3 wk/site/yr. Rates were best in line with the model Rs = 148 mL/d, with a standard deviation of 0.17 log units (factor 1.5). The POCIS canisters reduced mass transfer coefficients of the water boundary layer by a factor of 2 as measured by alabaster dissolution rates. A mechanistic model that accounts for flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…These values are fairly well in line with mass transfer equations for laminar flow over a flat surface (Stephens et al 2005): knormalw=0.664Dwnormalℓ(Uν)1/2(νDw)1/3where U is water flow velocity, ν is kinematic viscosity or water, and ℓ is average length of the flow lines over the sampler surface. Measured values of k w in a small headwater stream were fairly well in line with Equation 29 for a polar organic chemical integrative sampler (proportionality factor 0.41 instead of 0.664; Booij et al 2020). Equation 29 predicts k w between 1 and 25 µm/s for flow velocities of 1 to 100 cm/s at 20 °C, and ℓ between 2 and 20 cm, which corresponds to surface area normalized R s values between 0.9 and 22 L/(dm 2 d) for fully WBL‐controlled kinetics.…”
Section: Field Monitoring With Polymeric Samplerssupporting
confidence: 71%
See 2 more Smart Citations
“…These values are fairly well in line with mass transfer equations for laminar flow over a flat surface (Stephens et al 2005): knormalw=0.664Dwnormalℓ(Uν)1/2(νDw)1/3where U is water flow velocity, ν is kinematic viscosity or water, and ℓ is average length of the flow lines over the sampler surface. Measured values of k w in a small headwater stream were fairly well in line with Equation 29 for a polar organic chemical integrative sampler (proportionality factor 0.41 instead of 0.664; Booij et al 2020). Equation 29 predicts k w between 1 and 25 µm/s for flow velocities of 1 to 100 cm/s at 20 °C, and ℓ between 2 and 20 cm, which corresponds to surface area normalized R s values between 0.9 and 22 L/(dm 2 d) for fully WBL‐controlled kinetics.…”
Section: Field Monitoring With Polymeric Samplerssupporting
confidence: 71%
“…Assuming that transport in the membrane is via the pore space only, k m+w is given by (Booij et al 2020):…”
Section: Extraction Disks With Membranementioning
confidence: 99%
See 1 more Smart Citation
“…While Booij and Chen showed that a difference of cavity from 20 to 3–7 mm (polycarbonate design) does not largely impact the uptake of atrazine, Lobpreis et al showed that this same difference can impact the uptake up to a factor of 2. The use of other housings designs (POCIS) and canisters was shown to lead to proportionality coefficients that are much lower (0.41 for POCIS and 0.21 for POCIS inside canisters), revealing that eq would not be appropriate for these situations …”
Section: Resultsmentioning
confidence: 99%
“…The use of other housings designs (POCIS) and canisters was shown to lead to proportionality coefficients that are much lower (0.41 for POCIS and 0.21 for POCIS inside canisters), revealing that eq 10 would not be appropriate for these situations. 45 To refine the provided semi-empirical model, two aspects should be further studied. First, data obtained at the two lowest velocities (5 and 12 cm s −1 ) were below the regression lines, whereas data obtained at the two highest velocities (20 and 40 cm s −1 ) were above the regression line (Figure 4).…”
Section: ■ Results and Discussionmentioning
confidence: 99%